Ensuring sustainability in Libya with renewable energy and pumped hydro storage - Elmnifi, Monaem; Khaleel, Mohamed; Vambol, Sergij; Yeremenko, Sergiy; Nassar, Yasser F.; Dzhulai, Oleksandr (Ecological Questions, 2024)
A radical transformation is occurring in the global energy system, with solar PV and wind energy contributing to three-quarters of new electricity generation capacity due to their affordability. This shift towards renewable electrification of energy services, such as transportation, heating, and industry, will gradually replace fossil fuels in the coming decades. This paper highlights Libya's potential to achieve energy self-sufficiency in the twenty-first century. In addition to its fossil energy resources, Libya possesses favourable conditions for solar, wind, and moderate hydroelectric energy. The solar energy potential alone is approximately 100 times greater than what is needed to support a fully solar-powered system that provides energy consumption similar to developed countries for all Libyan citizens, without relying on fossil fuels. Moreover, Libya's Green Mountain range offers substantial opportunities for low-cost pumped off-river hydropower storage. Therefore, the integration of solar and wind energy, complemented by hydropower and battery storage, is likely to be the primary pathway for the rapid growth of Libya's renewable electricity sector.